Au based Ni and Co bimetallic core shell nanocatalysts for room temperature selective decomposition of hydrous hydrazine to hydrogen - Jain, P.; Anila, K. A.; Vinod, C. P. (ChemistrySelect, 2019)
Nickel and Cobalt bimetallic catalysts with Au as core metal has been synthesized and demonstrated for hydrazine decomposition reaction for producing hydrogen. Gold-cobalt and gold nickel bimetallic system belonging to the class of strained structures with high lattice mismatch of approximately 14% are demonstrated for synergistic effects atypical of monometallic counterparts for the selective decomposition of hydrous hydrazine to H-2 with N-2 as the other product at room temperature.
Keywords: (HDR); Au@Co.; Au@Ni.; Bimetallic; catalyst.; core; decomposition; Hydrazine; nanoparticles.; reaction; shell